Potensi Kesulitan-Kesulitan Yang Dihadapi Siswa SMK Saat Menyelesaikan Masalah Materi Sistem Persamaan Linear Dua Variabel: Studi Eksploratif - Desi Aprianti; Purna Bayu Nugroho; Venty Meilasari (International Journal of Progressive Mathematics Education, 2022)
This study aims to determine the difficulties of concepts and principles experienced by students in solving story problems of a system of linear equations of two variables for class X at SMK Muhammadiyah 1 Kotabumi and the factors that cause students to experience these difficulties. The method used in this research is descriptive method in the form of case studies. The subjects used in this study were several students of class X. The tool used was a written test in the form of an essay. From the analysis of the data it is known that the difficulties and factors that cause the difficulties experienced by students. Difficulty eg variable terms, difficulty changing story problems into mathematical sentences, difficulty performing operations with elimination and substitution methods, difficulty operating subtraction and addition, difficulty changing variable replacement values into question sentences. Factors causing difficulties were lack of mastery of SPLDV material, lack of accuracy when working on questions, and not mastering SPLDV concepts and principles. Â  Penelitian ini bertujuan untuk mengetahui kesulitan konsep dan prinsip yang dialami siswa dalam menyelesaikan soal cerita sistem persamaan linear dua variabel kelas X di SMK Muhammadiyah 1 Kotabumi dan faktor yang menyebabkan siswa mengalami kesulitan tersebut. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan bentuk studi kasus. Subjek yang digunakan dalam penelitian ini adalah beberapa siswa kelas X. Alat yang digunakan adalah ialah tes tertulis yang berbentuk essai. Dari analisis data diketahui kesulitan dan faktor penyebab kesulitan yang dialami siswa. Kesulitan memisalkan istilah variabel, kesulitan mengubah soal cerita kedalam kalimat matematika, kesulitan melakukan operasi dengan metode eliminasi dan substitusi, kesulitan mengoprasikan pengurangan dan penjumlahan, kesulitan mengubah nilai pengganti variabel ke dalam kalimat pertanyaan. Faktor penyebab kesulitan yakni kurangnya penguasaan materi SPLDV, kurangnya ketelitian saat pengerjaan soal, serta tidak menguasai konsep dan prinsip SPLDV.